Anisotropic non-Fermi liquid and dynamical Planckian scaling of a quasi-kagome Kondo lattice system - Shin-ichi Kimura; Muhammad Frassetia Lubis; Hiroshi Watanabe; Yasuyuki Shimura; Toshiro Takabatake (npj Quantum Materials)
Abstract At the quantum critical point of correlated materials, a non-Fermi liquid state appears where electron correlations continuously develop to very low temperatures. The relaxation time of the interacted electrons, namely quasiparticles, is scaled with the Planckian time, ℏ/k B T. However, there is a debate over whether heavy-fermion systems can obey the Planckian time. In the optical conductivity spectra, the Drude response will appear as the scaling of ℏ ω/k B T as the dynamical Planckian scaling (DPS). Here, we report the non-Fermi liquid behavior in the Drude response of a candidate for such materials, the quasi-kagome Kondo lattice CeRhSn. Even though the material shows a strong valence fluctuation, renormalized Drude responses observed at the photon energy below 100 meV are characterized by non-Fermi-liquid-like scattering rate 1/τ. The heavy carriers’ Drude response only for the Ce quasi-kagome plane obeyed DPS below 80 K, suggesting the anisotropic quantum criticality with the strong c-f hybridization.